Re-Contextualization of Effectiveness and Efficiency in Post-Socialist Education - Rimantas Želvys (BCES Conference Books, 2018)
Transformation of post-socialist educational systems is perhaps one of the most interesting and at the same time underestimated in its importance, developments in the history of comparative education. After the three decades of post-socialist development one can note significant differences between the countries which once had identical or very similar educational systems. Perhaps the most interesting topic for comparativists to explore is the question: why instead of convergence do we observe the increasing divergence of education in the post-socialist area? One of the possible answers is that post-socialist countries perceived the new ideology, namely, the ideology of neoliberalism, in their own specific way, which was determined by their historical, cultural and religious heritage. The concepts of effectiveness and efficiency in education can be considered as one of the typical cases of re-contextualization. The paper provides several examples showing that these concepts are still interpreted in different ways in the East and in the West.